A review: Trends in Additive Manufacturing - Ahmed, F.; Syed, T.; Ashraf, M.; Adeel, S. (The Nucleus, 2022)
Additive manufacturing (AM), familiar as 3-D printing, is converting global manufacturing. AM technology is changing the dynamics of the design and production capability of the manufacturing industry. The continuous growth and the positive results demonstrate that additive manufacturing has a considerable place in the future of manufacturing. A large number of matters and materials can be printed because of the progression extremity in additive manufacturing technology (AMT). The returns of three-dimensional printing techniques will keep up to occur by ongoing research activities to minimize the restrictions that constraint the use of this technology. The flexibility of design customization and reduction in wastedge of material are the main advantages of AM. The capability to fabricate multifaceted compositions along with rapid fabrication of modes are also major paybacks of AM technology. Enhancement in accuracy is required to ensure the requirement of a finishing process. A study was conducted to review the strength of the products made through additive manufacturing processes. In addition, a broad-ranging review of the major 3D printing procedures/techniques and evolution towards their uses have been presented in this review. The advanced uses of AM in the field of aerospace industry, biological equipment, construction, buildings, and preventative structures are discussed. Advanced materials development includes polymer composites, metal and their alloys, ceramics and concrete was are also elaborated. In this study, we have considered the major operational challenges and the drawbacks of the layer-by-layer appearances in computer design. In general, this article provides an analysis of 3D printing, comprises of this technology, its advantages and limitations as a criterion for further growth/progress.